Characteristics of medical procedures performed by firefighters. - Rafał Wiszniewski; Chiara Gorgone (Critical Care Innovations, 2019)
INTRODUCTION: National Firefighting Rescue System (NFRS) often supports the Emergency Medical Service (EMS) units. If EMS is not yet at the scene, firefighters are able to perform necessary medical procedures while waiting for an ambulance. The aim of the study was to define the profile of patients based on experience of Polish Professional Fire Services (PFS). MATERIAL AND METHODS: 123 interventions were studied when firefighters arrived on the scene before ems, carried out in 2017 by PFS unit located in centre of Poland. For this retrospective study were analyzed a total of 100 complete and readable "rescue procedure charts" filled out by PFS firefighters. They were studied time of arrival, patients' demographic (age and sex), type of injury/ illness, type of medical procedures carried out by firefighters and duration of taking care of the patient before EMS arrival as well as types of equipment used during interventions. RESULTS: A total of 100 patients were included in the analysis (34 woman and 66 men). The mean age was 40.3 years (SD ± 16.56). The average time from arrival at the scene to initiation of medical procedures was 1.24 (SD ± 0.47) minutes. Before EMS arrival, firefighters were taking care of the patient for an average of 5.88 (SD ± 4.45) minutes. The most common type of injury was cervical spine trauma (41.34%), and the rarest condition was a hypothermia (19.23%). Cardiopulmonary resuscitation were performed in four cases. The most commonly used equipment were gloves (67.60%). The most common activity during taking care of patient were: psychological support (34.33%). CONCLUSIONS: During the interventions, firefighters perform rescue procedures mainly in case of injuries. The most common types of injuries include cervical spine and head trauma. Despite the fact that medical equipment is standardized in PFS units, some of the equipment are not used as often as the situations requires, which may result in a decrease in the effectiveness of rescue procedures.